2004
DOI: 10.18590/euscorpius.2004.vol2004.iss12.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of male Centruroides vittatus (Scorpiones: Buthidae) to aerial and substrate-borne chemical signals

Abstract: Chemical signaling promotes mate location throughout numerous animal taxa. In this study we investigated the possibility that striped scorpions, Centruroides vittatus, use chemical signaling in the form of odor plumes or substrate-borne deposits as communication channels. A Y-shaped arena was constructed to test scorpions' use of airborne chemical cues in the detection of potential mates. A second, circular behavioral choice chamber was used to test male scorpions' responses to female deposits by direct substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 5 publications
2
20
0
1
Order By: Relevance
“…We suggest their change in behavior was elicited by contact pheromones on the substrate, not volatile pheromones, because males did not alter their behavior until they were positioned directly over areas females had previously occupied. This is consistent with previous findings that scorpions do not respond to volatile pheromones (Benton 1992;Brownell 1992, 2001;Steinmetz et al 2004). Theoretically, through sexual selection, males may use female pheromones and increase the number of encounters with females by directing their movements once they come in contact with the pheromones, as demonstrated by Gaffin and Brownell (2001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We suggest their change in behavior was elicited by contact pheromones on the substrate, not volatile pheromones, because males did not alter their behavior until they were positioned directly over areas females had previously occupied. This is consistent with previous findings that scorpions do not respond to volatile pheromones (Benton 1992;Brownell 1992, 2001;Steinmetz et al 2004). Theoretically, through sexual selection, males may use female pheromones and increase the number of encounters with females by directing their movements once they come in contact with the pheromones, as demonstrated by Gaffin and Brownell (2001).…”
Section: Discussionsupporting
confidence: 92%
“…Gaffin and Brownell (1992) and Melville et al (2003) found that males responded positively to areas exposed to female conspecifics in Paruroctonus mesaensis (Scorpionida, Vaejovida) and Hadrurus arizonensis (Scorpionida, Iuridae), respectively. Males did not, however, demonstrate such a preference in a third study with Centruroides vittatus (Scorpionida, Buthidae) but Steinmetz et al (2004) suggested that males changed their behavior in areas previously exposed to female conspecifics. Melville et al (2003), in the only study to date to examine behavioral responses of males to conspecific males, found a non-significant preference for areas exposed to conspecific males.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Polis and Sissom (1990) suggested that the use of pheromones in the recognition and detection of potential partners is crucial for the mating success of many scorpion species. Numerous works have tested the detection of contact pheromones in scorpions (e.g., Benton, 1992;Gaffin & Brownell, 1992Melville et al, 2003;Miller & Formanowicz, 2011;Steinmetz et al, 2004;Taylor et al, 2012). Conversely, only a few studies have analyzed the use of volatile chemical signals in scorpions.…”
Section: Discussionmentioning
confidence: 99%
“…Scorpions have a pair of sexually dimorphic mechanosensory and chemosensory appendages, the pectines (Gaffin & Brownell, 1997;Kladt, Wolf, & Heinzel, 2007;Polis & Sissom, 1990;Stahnke, 1973), which seem to mediate chemically mediated orientation behaviors such as substrate scanning before and during mating (Gaffin & Brownell, 1992;Mineo & Del Claro, 2006;Tallarovic, Melville, & Brownell, 2000). Studies in several species of scorpions show that they can use chemical signaling to find potential mates and begin courtship (Gaffin & Brownell, 1992Melville, Tallarovic, & Brownell, 2003;Steinmetz, Bost, & Gaffin, 2004;Taylor, Cosper, & Gaffin, 2012). In many scorpion species, males transfer a mating plug after sperm transfer and this plug may be of different types and effectiveness (Peretti, 2010).…”
mentioning
confidence: 99%